2016
DOI: 10.1097/aln.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Myasthenia Gravis Influences the Relationship between Train-of-four Ratio and Twitch Tension and Run-down of Rat Endplate Potentials

Abstract: Background Train-of-four ratio (TOFR) is often used to evaluate muscle relaxation caused by neuromuscular-blocking agents (NMBAs). However, it is unknown whether TOFR reliably correlates with the first twitch tension (T1) in patients with myasthenia gravis (MG). By using rat models of experimental autoimmune MG (EAMG), the authors verified the hypothesis that the severity of MG influences the relationship between TOFR and T1. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It was found that while T1 of the TOF decreased to the same extent in severe and moderate groups, the TOF ratio in the severe group did not decrease to the same extent that the moderate group value did. The researchers concluded that the discrepancy in TOF ratio changes can cause an overestimation of recovery from NMB [ 15 ]. In our patient, despite unchanged TOF ratios, an obvious clinical improvement was noted following 4 mg of neostigmine and the second dose of sugammadex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that while T1 of the TOF decreased to the same extent in severe and moderate groups, the TOF ratio in the severe group did not decrease to the same extent that the moderate group value did. The researchers concluded that the discrepancy in TOF ratio changes can cause an overestimation of recovery from NMB [ 15 ]. In our patient, despite unchanged TOF ratios, an obvious clinical improvement was noted following 4 mg of neostigmine and the second dose of sugammadex.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, rapid reversal was observed with adequate TOF restoration. Both patients were observed for a period of 30-40 minutes to ensure that no residual curarization was present before extubation was performed [ 15 ]. Literature supports the use of sugammadex in MG patients receiving non-depolarizing steroidal NMBAs for surgery to prevent postoperative MC.…”
Section: Discussionmentioning
confidence: 99%
“…In the early onset stage of this MG, autoimmune antibodies in situ masking the membrane receptors induced the AChRs internalization and depression at the crest [ 122 ]. In the moderate and severe group, followed by systematic destruction, the receptor-containing crests of the JFs were destructed, and the JFs were degenerated, which resulted in the post-synaptic membrane was simplification [ 123 ]. In LG2 agrin mutation-induced MG, biopsy results from the right deltoid muscle showed that the JFs were simplified, and the diameter of the primary and secondary synaptic clefts was increased [ 124 ].…”
Section: Jfs Disorders In Nmj Related Diseasesmentioning
confidence: 99%